Use of institutional criteria for transcatheter device closure of Fontan fenestration - Midterm outcomes - Nikhil Thatte; Vivian Dimas; Alan Nugent; Thomas Zellers; Joseph Forbess; Luis Zabala; Song Zhang; Surendranath R Veeram Reddy (Wolters Kluwer Medknow Publications, 2020)
Background: There are no established criteria to decide suitability for Fontan fenestration closure. Our institution has the following criteria: an unobstructed Fontan pathway with no significant decompressing venovenous collaterals, baseline Fontan pressure ≤15 mmHg, baseline cardiac index ≤2 L/min/m2, and a decrease in cardiac index ≥20% with test occlusion of the fenestration. Objective: The objective of the study was to review midterm outcomes following device closure of Fontan fenestration using institutional criteria. Materials and Methods: A retrospective review was performed of patients who underwent catheterization with prior fenestrated Fontan procedure between May 2005 and January 2015. Patients were classified as those who underwent successful closure (A), had closure deferred due to failure to meet criteria (B), or were not referred for closure (C). Results: There were 42 patients in Group A, 10 in Group B, and 150 in Group C. The mean Fontan pressure increased from 13.1 ± 2.1 to 14.5 ± 2.1mmHg in Group A and 14.6 ± 1.5 to 15.7 ± 2.2 mmHg in Group B (P = not significant). With test occlusion, cardiac index fell by 18.12% ± 15.68% in Group A and 33.75% ± 14.98% in Group B (P = 0.019). At a median of 46 month follow-up, oxygen saturation increased significantly from 85.15% ± 6.29% at baseline to 94.6% ± 4.43% (P < 0.001) in Group A but with no statistically significant difference in the rates of plastic bronchitis, protein-losing enteropathy, stroke, or heart transplantation between the three groups. Conclusions: Using institutional criteria, transcatheter device closure of Fontan fenestration was followed by significant increase in oxygen saturations and no statistically significant difference in morbidity or mortality between closure and nonclosure groups.